DEVELOPMENT AND IN VITRO CHARACTERIZATION OF GASTRO RETENTIVE RAFT FORMING STAVUDINE TABLETS (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The objective of the present investigation was to identify a suitable raft forming agent and to develop raft forming stavudine matrix tablets using different rate controlling natural, semi-synthetic and synthetic polymers to achieve prolonged gastric residence time, leading to an increase in drug bioavailability and patient compliance. Various raft forming agents were used in preliminary screening. Raft forming floating tablets were developed using pullulan gum as natural rate controlling polymer, and directly compressible grades of hydroxypropyl methylcellulose (Benecel K4M DC) as semi synthetic, and Carbopol 71G as synthetic rate controlling polymers respectively and optimum concentrations of sodium-bicarbonate as gas generating agent to generate optimum buoyancy by direct compression method. Raft forming tablets were evaluated for weight variation, thickness, hardness, friability, drug content, in vitro drug release, floating buoyancy and raft strength. Drug-excipients compatibility study showed no interaction between drug and excipients. Raft forming tablets showed satisfactory results when evaluated for weight variation, thickness, hardness, friability, drug content, and raft strength. The optimized formulation was selected based on physicochemical characteristics and in vitro drug dissolution characteristics. Further, the optimized formulation was evaluated for in vivo radiographic studies by incorporating BaSO4 as radio opaque substance. Optimized formulation showed controlled and prolonged drug release profiles while floating and raft formation over the dissolution medium. Diffusion followed by erosion with raft forming drug release mechanism was observed for the formulation, indicating that dissolution media diffusion and polymer erosion played an essential role in drug release. In vivo radiographic studies revealed that the raft forming formulations remained in the stomach for 240 ± 30 min in rabbits and indicated that gastric retention time was increased by the floating and raft forming principle, which was considered and desirable for absorption window drugs.